BUDAYA ORGANISASI DAN DAMPAKNYA TERHADAP LEMBAGA PENDIDIKAN - Muhammad Rizal Al Hairi; Syahrani (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
Organizational culture is the foundation for the formation of an organization, because organizational culture is the identity of an organization. There are several opinions about the notion of organizational culture, the most popular opinion is that organizational culture is the subject of solving external and internal problems. It is understood that the organization was founded to solve a problem. An education usually has an organization. Organizations in education have roles that can help support the quality of education. One of these roles is helping the role of teachers in improving the quality of human resources for students. Organization is an important component in life, especially in the sphere of education. Therefore, it should be grateful for the existence of an organization in life. Without organization, mankind may have difficulty in solving a problem.